Applied analysis of ultrasound-guided ilioinguinal and iliohypogastric nerve blocks in the radical surgery of aged cervical cancer - Gu, Jianhua (Oncol Lett, 2017)
In the present study, we evaluated the effects of ultrasound-guided ilioinguinal and iliohypogastric nerve blocks and intratracheal general anesthesia in the radical surgery of aged cervical cancer. From June 2014 to December 2014, 62 patients diagnosed with aged cervical cancer were enrolled in this study. The patients conformed to the indication of cervical cancer radical surgery. Patients were randomly divided into the test group and the control group according to the random number table with 31 individuals in each group. General anesthesia and compound ultrasound-guided ilioinguinal and iliohypogastric nerve blocks were applied in the test group, while intratracheal general anesthesia was used in the control group. The results showed that the operative time, awake time and the total dosage of propofol and sufentanil in the test group were significantly lower than those in the control group. The postoperative VAS score, the times to press the automatic control bump and continuous application time of the automatic control bump in the test group were significantly less than those in the control group. The occurrence rate of anesthesia-related adverse reactions in the test group during the perioperative period was significantly lower than that in the control group. Differences were statistically significant (P<0.05). We concluded that ultrasound-guided ilioinguinal and iliohypogastric nerve blocks significantly improved the analgesic effects during the perioperative and postoperative period in cervical cancer radical surgeries.